The extra resource burden of in-hospital falls: A cost of falls study - Morello, R.; Barker, A.; Watts, J.; Haines, T.; Zavarsek, S.; Hill, Keith; Brand, C.; Sherrington, C.; Wolfe, R.; Bohensky, M.; Stoelwinder, J. (2015)
Objective: To quantify the additional hospital length of stay (LOS) and costs associated with in-hospital falls and fall injuries in acute hospitals in Australia. Design, setting and participants: A multisite prospective cohort study conducted during 2011–2013 in the control wards of a falls prevention trial (6-PACK). The trial included all admissions to 12 acute medical and surgical wards of six Australian hospitals. In-hospital falls data were collected from medical record reviews, daily verbal reports by ward nurse unit managers, and hospital incident reporting and administrative databases. Clinical costing data were linked for three of the six participating hospitals to calculate patient-level costs. Outcome measures: Hospital LOS and costs associated with in-hospital falls and fall injuries for each patient admission. Results: We found that 966 of a total of 27 026 hospital admissions (3.6%) involved at least one fall, and 313 (1.2%) at least one fall injury, a total of 1330 falls and 418 fall injuries. After adjustment for age, sex, cognitive impairment, admission type, comorbidity and clustering by hospital, patients who had an in-hospital fall had a mean increase in LOS of 8 days (95% CI, 5.8–10.4; P < 0.001) compared with non-fallers, and incurred mean additional hospital costs of $6669 (95% CI, $3888–$9450; P < 0.001). Patients with a fall-related injury had a mean increase in LOS of 4 days (95% CI, 1.8–6.6; P = 0.001) compared with those who fell without injury, and there was also a tendency to additional hospital costs (mean, $4727; 95% CI, −$568 to $10 022; P = 0.080). Conclusion: Patients who experience an in-hospital fall have significantly longer hospital stays and higher costs. Programs need to target the prevention of all falls, not just the reduction of fall-related injuries.